Age and growth rate estimations of the commercially fished gastropod Buccinum undatum. (30th July 2018) - Hollyman, Philip R; Chenery, Simon R N; Leng, Melanie J; Laptikhovsky, Vladimir V; Colvin, Charlotte N; Richardson, Christopher A; ,
Abstract: Calculating age and growth rate for the commercially important whelk, Buccinum undatum in the aid of fishery management has historically been undertaken using growth rings on the organic operculum. This is difficult due to their poor readability and confusion between two different sets of growth lines present. Recent work presented the calcium carbonate statolith as an alternative for age determination of B. undatum . Here we compare the use of statoliths and opercula, comparing their readability and creating growth curves for three distinct populations across the United Kingdom. Using these data, we also test the most appropriate growth equation to model this species. Lastly, we use oxygen isotope analysis of the shells to assign accurate ages to several individuals from each site. These data were used to test the accuracy of statolith and operculum ages. Statoliths, whilst more time consuming to process have improved clarity and accuracy compared with the opercula. This improved readability has highlighted that a Gompertz growth function should be used for populations of this species, when in past studies, von Bertalanffy is often used. Statoliths are a viable improvement to opercula when assessing B. undatum in the context of fishery monitoring and management.